MELD-XI Score Is Associated With Short-Term Adverse Events in Patients With Heart Failure With Preserved Ejection - Wang, Sunying; Wang, Yuwei; Luo, Manqing; Lin, Kaiyang; Xie, Xiaoxu; Lin, Na; Yang, Qingyong; Zou, Tian; Chen, Xinan; Xie, Xianwei; Guo, Yansong (Frontiers in Cardiovascular Medicine, 2021)
Aim: Accumulating evidence suggests that MELD-XI score holds the ability to predict the prognosis of congestive heart failure. However, most of the evidence is based on the end-stage heart failure population; thus we aim to explore the association between MELD-XI score and the prognosis in heart failure with preserved ejection fraction (HFpEF). Methods: A total of 30096 patients hospitalized for HFpEF in Fujian Provincial Hospital between January 1, 2014 and July 17, 2020 with available measures of creatinine and liver function were enrolled. The primary endpoint was 60-day in-hospital all-cause mortality. Secondary endpoints were 60-day in-hospital cardiovascular mortality and 30-day re-hospitalization for heart failure. Results: A total of 222 patients died within 60 days after admission, among which 75 deaths were considered cardiogenic. And 73 patients were readmitted for heart failure within 30 days after discharge. Generally, patients with elevated MELD-XI score tended to have more comorbidities, higher NYHA class and higher inflammatory biomarkers levels. Meanwhile MELD-XI score was positively correlated with NT-pro BNP, left atrial diameter, E/e’ and negatively correlated with LVEF. After adjusting for conventional risk factors, MELD-XI score was independently associated with 60-day in-hospital all-cause mortality (hazard ratio(HR)=1.052, 95% confidential interval(CI) 1.022-1.083, P=0.001), 60-day in-hospital cardiovascular mortality (HR=1.064, 95% CI 1.013-1.118, P=0.014) and 30-day readmission for heart failure (HR=1.061, 95% CI 1.015-1.108, P=0.009). Furthermore, MELD-XI score added incremental discriminatory capacity to risk stratification models developed based on this cohort. Conclusion: MELD-XI score was associated with short-term adverse events and provided additional discriminatory capacity to risk stratification models in patients hospitalized for HFpEF.